(untitled) (International Journal of Food and Nutritional Sciences, 2022)
The labeling of graphs has been applied in the fields such as circuit design, communication network, coding theory, and crystallography. In the domain of Mathematics, graph theory is the study of graphs that concerns with the relationship among edges and vertices. Graphs are one of the prime objects of study in discrete Mathematics. Labeling of graphs is an active research area, it has been widely studied by several researchers. In a wide area network (WAN), several systems are connected to the main server, the labeling technique plays a vital role to label the cables.